THE INFLUENCE OF ISLAMIC ORGANIZATIONAL CULTURE AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS MODERATING - Muhsoqih, Mas Bagus; Pratama, Abdul Aziz Nugraha (Journal of Islamic enterpreneurship and Management, 2021)
This research is motivated by the banking world which has entered the era of globalization, where company competition is getting tougher. So that every company is required to improve the things that exist within the company so that it can develop and get better. Human resource management is very important and becomes the focus of many organizations in competitive advantage. The purpose of this study is to determine and analyze the influence of Islamic Organizational Culture on Employee Performance with Variables as Moderating on Employees of BRI Syariah KC Semarang.In this study using quantitative methods by processing primary data through a questionnaire given to employees of BRI Syariah KC Semarang 40 respondents with a saturated sample technique. The data obtained were processed using SPSS version 21. The analysis used in this study included instrument tests, statistical tests, classical assumption tests, and MRA.Results Based on the research test, it was found that: (1) Islamic Organizational Culture had a negative and insignificant effect on employee performance at BRI Syariah KC Semarang. (2) Compensation has a positive and significant effect on employee performance at BRI Syariah KC Semarang. (3) Motivation cannot moderate the influence of Islamic Organizational Culture on Employee Performance at BRI Syariah KC Semarang. (4) Motivation cannot moderate the effect of compensation on employee performance at BRI Syariah KC Semarang..